Penerapan Cooperative Learning untuk Meningkatkan Hasil Belajar Seni Musik - Niltufarichah, Niltufarichah; Djatiprammbudi, Djuli; Harmanto, Harmanto (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2024)
This study aims to analyse the application of the Cooperative Learning model in improving student learning outcomes in Music Arts subjects. Cooperative Learning is a collaborative learning approach that encourages students to work in groups to achieve shared learning goals. In the context of Music Arts, this model provides opportunities for students to share ideas, explore creativity, and develop musical skills through collaboration. The research method used is quasi-experiment with control group design and experiment. The results show that the application of Cooperative Learning can significantly improve learning outcomes compared to conventional learning methods. In addition, students showed increased learning motivation, communication skills, and active participation during the learning process. These findings show that Cooperative Learning is effectively used to teach the art of music with a creative, collaborative, and fun approach.